(untitled) (European Journal of Economics, Finance and Business Development, 2024)
In the competitive landscape of the healthcare industry, medical enterprises must continuously adapt and innovate to maintain and enhance their market position. This study examines strategic enhancements designed to improve the management of competitiveness in medical institutions. By analyzing current industry practices and identifying key success factors, this research provides a comprehensive overview of effective strategies tailored for healthcare enterprises. Key areas of focus include the integration of advanced healthcare technologies, optimization of resource management, and the cultivation of a patient-centric culture. The study also emphasizes the importance of data-driven decision-making and continuous improvement processes to foster strategic agility. By implementing these strategic enhancements, medical enterprises can achieve superior quality of care, heightened patient satisfaction, and operational efficiency, ultimately ensuring long-term sustainability and competitive advantage in the dynamic healthcare environment.